The Effect of Outpatient Service Quality on Patient Satisfaction with Perceived Value as a Mediating Variable - Nurwestu Rusetiyanti; Eric Harianto (AIBPM Publisher, 2025)
Attention to the quality of healthcare services has increased significantly. Healthcare providers are competing to deliver higher-quality healthcare services. Management is required to focus not only on medical technicalities but also on creating perceived value that drives patient satisfaction. Acknowledged as a central metric of healthcare service excellence, patient satisfaction is analyzed in this inquiry alongside the impact of outpatient service quality and perceived value at Nima Medical Center Clinic. The investigation also explores the function of perceived value as an intervening factor in the association between outpatient service quality and patient satisfaction. A quantitative approach was adopted, employing a survey instrument with a 1–5 Likert scale on 96 purposively sampled patients from the Nima Medical Center Clinic in Yogyakarta. Data were initially tabulated in Excel and subsequently analyzed using SmartPLS 4.0, employing the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique. Evidence shows that outpatient service excellence has a positive but not statistically significant direct link to patient satisfaction. Conversely, perceived worth exerts a robust, significant direct impact on contentment. Notably, the influence of service excellence on satisfaction is significant when it is facilitated by perceived worth. Altogether, these outcomes underscore the vital role of perceived value as a mediating factor between service excellence and patient satisfaction. Consequently, a favorable assessment of service value is essential to improve patient satisfaction in the outpatient department.